Adorno, o fascismo e o mal - Bueno, Sinésio Ferraz (Editora Oficina Universitária, 2021)
One of the thinkers of the 20th century who most devoted himself to the critical study of fascism was the German philosopher and sociologist Theodor Adorno. His work detailed the emotional vulnerability of ordinary citizens to prejudices, appeals to group membership and destructive rage directed against victims of fascist persecution. In carrying out his critical analysis, Adorno mainly employed concepts from Freudian psychoanalysis and dialectical materialism. This book presents Adorno's critical study of fascism, but also seeks to demonstrate that the destructiveness and cruelty of fascism go beyond the analysis proposed by Adorno, and therefore require the use of the concept of metaphysical evil for its broader understanding. With this objective, the first part of the work exposes the central theoretical elements used by Adorno to understand and criticize fascism. In the second part, the most important philosophical concepts are exposed to understand the metaphysical concept of evil and also its implications related to the field of education.